Gardner Denver - Elias, Jaan; Quinn, James, active 2020; Blumenthal, Adam (London : Yale School of Management, 2020)
As KKR, a private equity firm, prepared to take Gardner-Denver, one of its portfolio companies, public in mid-2017, a discussion arose on the Gardner-Denver board about the implications of granting approximately $110 million in equity to its global employee base as part of its innovative "broad-based employee ownership program".
Orginally Published InElias, J., Quinn, J., & Blumenthal, A. (2020). Gardner Denver. 20-039. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Employee ownership -- Case studies; Incentives in industry -- Case studies; Stock ownership -- Case studies